Komik Sebagai Refleksivitas Sosial Bangsa Indonesia - Segara, Putu Agung Danu (Peneliti.net, 2023)
Comics contain a graphic aspect, illustration is an image art that is used to visually explain an intention or purpose. The purpose of the study of comics as an instrument of social reflexivity of the Indonesian nation is that in the future we should be able to act and make art in the process of nation building in a better direction by not abandoning historical values and national identity. The data in the study of